Validity and reliability of a Malay version of the brief illness perception questionnaire for patients with type 2 diabetes mellitus - Chew, Boon-How; Vos, Rimke C.; Heijmans, Monique; Shariff-Ghazali, Sazlina; Fernandez, Aaron; Rutten, Guy E. H. M. (Springer Nature, 2017)
BACKGROUND:Illness perceptions involve the personal beliefs that patients have about their illness and may influence health behaviours considerably. Since an instrument to measure these perceptions for Malay population in Malaysia is lacking, we translated and examined the psychometric properties of the Malay version of the Brief Illness Perception Questionnaire (MBIPQ) in adult patients with type 2 diabetes mellitus.METHODS:The MBIPQ has nine items, all use a 0-10 response scale, except the ninth item about causal factors, which is an open-ended item. A standard procedure was used to translate and adapt the English BIPQ into Malay language. Construct validity was examined comparing item scores and scores on the Diabetes Management Self-Efficacy Scale, the Morisky Medication Adherence Scale, the World Health Organization Quality of Life-brief, the 9-item Patient Health Questionnaire, the 17-item Diabetes Distress Scale, HbA1c and the presence of complications. In addition, 2-week and 4-week test-retest reliability were studied.RESULTS: A total of 312 patients completed the MBIPQ. Out of this, 97 and 215 patients completed the 2- or 4-weeks test-retest reliability questionnaire, respectively. Moderate inter-items correlations were observed between illness perception dimensions (r = -0.31 to 0.53). MBIPQ items showed the expected correlations with self-efficacy (r = 0.35), medication adherence (r = 0.29), quality of life (r = -0.17 to 0.31) and depressive symptoms (r = -0.18 to 0.21). People with severe diabetes-related distress also were more concern (t-test = 4.01, p < 0.001) and experienced lower personal control (t-test = 2.07, p = 0.031). People with any diabetes-related complication perceived the consequences as more serious (t-test = 2.04, p = 0.044). The 2-week and 4-week test-retest reliabilities varied between ICCagreement 0.39 to 0.70 and 0.58 to 0.78, respectively. CONCLUSIONS:The psychometric properties of items in the MBIPQ are moderate. The MBIPQ showed good cross-cultural validity and moderate construct validity. Test-retest reliability was moderate. Despite the moderate psychometric properties, the MBIPQ may be useful in clinical practice as it is a useful instrument to elicit and communicate on patient's personal thoughts and feelings. Future research is needed to establish its responsiveness and predictive validity.